2014
DOI: 10.1177/1533317514539379
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Melatonin Agonist for Delirium in the Elderly Patients

Abstract: The objective of this review is to summarize the available data on the use of melatonin and melatonin agonist for the prevention and management of delirium in the elderly patients from randomized controlled trials (RCTs). A systematic search of 5 major databases PubMed, MEDLINE, PsychINFO, Embase, and Cochrane Library was conducted. This search yielded a total of 2 RCTs for melatonin. One study compared melatonin to midazolam, clonidine, and control groups for the prevention and management of delirium in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
(81 reference statements)
0
22
0
1
Order By: Relevance
“…Currently, guidelines on melatonin supplementation dosage are limited. The exact dose of melatonin used in different clinical trials ranges from 0.5 mg to 10 mg daily 47 . In the present meta‐analysis, subgroup analyses indicated that a higher dose of melatonin (5 mg) might be more beneficial for the prevention of POD.…”
Section: Discussionmentioning
confidence: 68%
“…Currently, guidelines on melatonin supplementation dosage are limited. The exact dose of melatonin used in different clinical trials ranges from 0.5 mg to 10 mg daily 47 . In the present meta‐analysis, subgroup analyses indicated that a higher dose of melatonin (5 mg) might be more beneficial for the prevention of POD.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast to patients who are treated in curative intent and where the fast tapering and stopping of neuroleptics and benzodiazepines is of upmost importance once the symptoms are no longer severe, it may be appropriate to continue the medication specifically in patients in the last days of life and patients with structural brain lesions (i.e., metastases) and severe symptoms such as agitation. In major trial registries (i.e., clinicaltrials.gov), a number of trials assessing melatonin (68)(69)(70)(71)(72)(73) for the prophylaxis and treatment of delirium and have been registered and some are already recruiting (e.g., ClinicalTrials.gov Identifier: NCT02615340, NCT03013790, NCT02536417). Once data from these trials becomes available, these approaches may provide an interesting alternative to neuroleptics and benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%
“…[71415] In addition, it has been shown that melatonin is able to treat and prevent the ICU delirium. [1617]…”
Section: Discussionmentioning
confidence: 99%